Conserved allosteric sodium in class A GPCRs: Na+ dynamics in GPCR signaling - Katritch, Vsevolod “Seva” (Henry Stewart Talks, 2019)
Na+ dynamics in GPCR signaling, Mutations in Na+ pocket, Protonation changes, Allosteric Na+ pocket, Bitopic ligands